2014
DOI: 10.1016/j.rbmo.2013.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of WNT9B mutations in Chinese women with Mayer–Rokitansky–Küster–Hauser syndrome

Abstract: Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome is a rare congenital female genital anomaly, which is caused by aplasia of the caudalportion of the Müllerian duct. The WNT9B gene encodes a secretory glycoprotein essential for the caudal extension of the Müllerian duct during embryonic development in mice. Coding regions and exon/intron boundaries of the WNT9B gene were amplified and sequenced in 42 Chinese women with MRKH syndrome and 42 controls. Two novel heterozygous mutationswere identified,which were absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Although intensively studied, the outcomes of candidate gene analyses have generally been sparse [65]. Positive findings from molecular genetic analyses include mutations in LHX1 [41, 66], TBX6 [60, 67], RBM8A [67], and WNT9B [68, 69]. Finally, mutations in WNT4 have been reported in females with Müllerian aplasia and hyperandrogenism [26, 70, 71], although it is thought to be an entity that differs from MRKH syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Although intensively studied, the outcomes of candidate gene analyses have generally been sparse [65]. Positive findings from molecular genetic analyses include mutations in LHX1 [41, 66], TBX6 [60, 67], RBM8A [67], and WNT9B [68, 69]. Finally, mutations in WNT4 have been reported in females with Müllerian aplasia and hyperandrogenism [26, 70, 71], although it is thought to be an entity that differs from MRKH syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…We failed to replicate the 7 following previously reported variants: rs16826648 [10], c.697G>A [15] and c.483C>T [8] in WNT4; c.342C>T [10] and c.861G>A [8] in WNT7A; c.113C>G [18] in HOXA11; and c.791G>C [25] in LHX1. The remaining 5 variants (rs3749319 [10] and rs3762719 [10] in WNT7A; C.170A>G [17] in HOXA10; rs2070072 [14] in GALT; and c.*158C>T [16] in WNT9B) were detected, but there were no significant differences in the frequencies of these genotypes or alleles between the cases and controls in this Chinese cohort (Table 2). These discrepancies may be due to differences among the study populations assessed and genetic heterogeneity, which has been observed in previous studies, especially in studies of monozygotic twins [26, 27].…”
Section: Discussionmentioning
confidence: 82%
“…Mutations in WNT4 are associated with MRKHS and androgen excess. Furthermore, the studies of Wang et al [2014] and Waschk et al [2016] showed also an association between mutations [Morcel et al, 2007]. This interval contains the TBX6 gene (OMIM 602427) encoding a sequence-specific DNA transcription factor, which belongs to the T-box gene family [Wilson and Conlon, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that WNT4 mutations are causative for a subgroup of MRKHS with signs of hyperandrogenism [Biason-Lauber et al, 2004]. Recently, the studies of Wang et al [2014] and Waschk et al [2016] showed an association between mutations in WNT9B and disorders of the müllerian ducts.…”
mentioning
confidence: 99%